algebra solving log equations

posted by .

n sqrt(x-8)= 5

I would like help to solve this what i did was to take away the square root i squared both sides coming up with

(ln sqrt(x-8))^2= (5)^2

ln(x-8)=25

am i alowed to do this with ln in the equation?

then i subtract 8 from both sides

ln x = 17

e^(ln x)= e^17
e cancels out ln leaving with
x=e^17

this is not right the real answer is
x = 8 + e^10 on math-way but how?

thanks

  • algebra solving log equations -

    Ln sqrt(x-8) = 5

    Exponential form:
    e^5 = sqrt(x-8)
    Square both sides:
    e^10 = x-8
    X = 8 + e^10
























    exponential form:

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. radical equation

    2^x+20=15+3^x A)1 B)16 C)-5 D)25 I chose c but i got it wrong i am having a problem understanding it. Let me rewrite the question in a more standard format. 2* sqrt(x)+20=15 + 3*sqrt(x) where * means multiply, and sqrt means the square …
  2. MATH

    I need to simply this equation, but I got stuck. h/(4-sqrt(16+h)) = y First, I multiplied (4+sqrt(16+h)/(4+sqrt(16+h) to both sides, and I ended up with h(4+sqrt(16+h)/-h. Is this correct?
  3. math

    Solve for the indicated variable A=1/2 bh Solve for b 2A = bh, so b = 2A/h ok thanks so on this example C=2pie r Solve for R Would the answer be 2C/pie=r ?
  4. Algebra

    Solve for s: h=(square root of 3)times s/2 and solve for h V= (pi)r squared h / 3 Solve for s: h=(square root of 3)times s/2 Multiply both sides by 2. 2h = (sqrt 3)*s*2/2 which cancels the 2 on the right. 2h = (sqrt 3)*s Now divide …
  5. math

    determine the area of triangle abc when side ab= square root of x, side bc= square root of x, and side ca= the square root of the square root of x. So how do I solve it. How do I add the square root of x + the square root of x + the …
  6. Math

    How do you find a square root of a number that's not a perfect square?
  7. maths

    how do i solve this equation? 21(X-(1/7))^2= 3/7 thx Divide both sides by 21 Take the square root of both sides. Rewrite it as x - (1/7)= sqrt [(1/21)*(3/7)] = sqrt[(1/7)*(1/3)(1/7)] = (1/7) sqrt(1/3) x = (1/7)[1 + sqrt(1/3)] tahnks
  8. algebra

    simplify: square root of 5 + square root of 20 - square root of 27 + square root of 147. simplify: 6/4square root of 2 sqrt 5 + sqrt 20 - sqrt 27 + sqrt 147 = sqrt 5 + sqrt (4*5) - sqrt (3*9) + sqrt (49*3) = 3 sqrt 5 - 3 sqrt 3 + 7 …
  9. algebra 2

    Not sure if either one of these answer are correct to simplify the sqrt for 24 1) 24 = 6 x 4 square root of 24 = square root of 6 x 4 2 root 6 2) sq root 24 = sq root (4x6)= sqrt 4 x sqrt 6= 2sq root 6=4.89898 3) Square root of 24 …
  10. Pre-calc Solve logarithmic

    ln sqrt(x-8)= 5 I would like help to solve this what i did was to take away the square root i squared both sides coming up with (ln sqrt(x-8))^2= (5)^2 ln(x-8)=25 am i alowed to do this with ln in the equation?

More Similar Questions